Communal Rituals of the Nyakyusa - Wilson, Monica (Routledge, 2018)
Cover page -- Halftitle page -- Title page -- Copyright page -- Title page -- Copyright page -- Dedication -- CONTENTS -- MAPS, PLANS, AND TABLES -- LIST OF ILLUSTRATIONS -- ACKNOWLEDGMENT -- CHAPTER 1 INTRODUCTORY -- CHAPTER II THE MYTHOLOGICAL CHARTER -- CHAPTER III THE `DIVINE KINGS' -- (a) CHARACTERISTICS OF 'DIVINE KINGS' -- (b) LUBAGA -- (c) MBANDE -- (d) PALIKYALA -- CHAPTER IV THE RITUAL OF CHIEFTAINSHIP -- (a) THE 'COMING OUT -- (b) THE CHIEF'S MEDICINES -- (c) DEATH AND BURIAL OF A CHIEF -- (d) THE CHIEF AND THE 'BREATH OF MEN' -- (e) THE NECESSITY FOR HARMONY -- CHAPTER V SACRIFICES AT THE GROVES OF CHIEFS -- (a) THE PLACE, OCCASION, AND FORM OF SACRIFICE -- (b) SACRIFICE TO MWAIJONGA -- (c) SACRIFICE TO MWAKISAMBWE -- (d) SACRIFICE AT KABALE -- (e) MODERN CHANGES -- (f) THE FIRST FRUITS -- CHAPTER VI LAND AND POWER -- (a) THE TERRITORIAL ALIGNMENT OF CHIEFDOMS AND VILLAGES -- (b) THE BALANCE BETWEEN GENERATIONS AND SECTIONS -- (c) RITUAL AND SECULAR BONDS -- CHAPTER VII CLEANSING THE COUNTRY -- (a) THE RATS -- (b) THE GROUND HORNBILL -- (c) SMALLPOX -- (d) THE WILD PIG -- CHAPTER VIII RAIN-MAKING AND 'SPRINKLING THE HOMES TEADS' -- (a) RAIN MAGIC -- (b) MAGIC OF FERTILITY -- CHAPTER IX KASITILE THE PRIEST -- CHAPTER X MEDICINES -- (a) TYPES OF MEDICINES -- (b) MEDICINES AND MORALITY -- (c) DOCTORS -- (d) SYMBOLISM -- CHAPTER XI NYAKYUSA COSMOLOGY -- CHAPTER XII PAGAN AND CHRISTIAN -- (a) THE GROWTH OF A CHRISTIAN COMMUNITY -- (b) THE CHRISTIAN WITHDRAWAL -- (c) CHRISTIAN RITUAL AND DOGMA -- (d) 'INDEPENDENT' AFRICAN CHURCHES -- (e) THE CONTRAST BETWEEN PAGAN AND CHRISTIAN -- CHAPTER XIII TWENTY YEARS' CHANGE -- CHAPTER XIV RELIGION AND SOCIAL STRUCTURE -- MEMBERSHIP OF VILLAGES -- INDEX.